A prospective randomized comparative study between trochanteric versus piriformis entry portal for intramedullary interlock nailing in the treatment of femoral shaft fracture - Meena, Kanta Prasad; Yadav, Mahendra Kumar; Devatheya, Deepak (International Journal of Research in Orthopaedics, 2016)
Background: In case of close nailing for femoral shaft fractures, the nail is inserted into the medullary cavity through the proximal femur without disturbing the periosteal blood supply of at the fracture site. The piriformis fossa and greater trochanter has been commonly described as starting points for antegrade femoral nailing. The purpose of this study was to compare results of two entry ports being used for intramedullary nailing for femoral shaft fractures. Methods: This study was conducted during a period of one year. The patients admitted with femoral diaphyseal fractures for antegrade nailing were divided in two groups alternatively for piriformis fossa entry point and greater trochanter entry point. Total number of patient in each group was 25 (n = 25). Functional outcome were analyzed at final follow up using Hari’s hip score. Results: There was no significant difference clinical and functional output in both group but intraoperative time and fluoroscopic time was significant (P <0.001). Conclusions: Femoral nailing through the greater trochanter entry portal with specifically designed nails should be considered a rational alternative to femoral nailing compared to Piriformis fossa entry portal with the benefit of reduced requirement for fluoroscopy and decreased operative time in obese patients. Statistically no significant difference (>0.005) in clinical and Functional outcome based on Hari’s hip score.